2020
DOI: 10.1136/annrheumdis-2020-eular.891
|View full text |Cite
|
Sign up to set email alerts
|

Op0068 incidence and Prevalence of Rheumatoid Arthritis in Denmark: A Nationwide Population-Based Study Investigating the Effect of Four Different Case Definitions

Abstract: Background:The incidence rate (IR) and point prevalence (PP) of rheumatoid arthritis (RA) in Denmark is largely unknown. Two challenges in estimating the “true” IR and PP using nationwide registry data are the choice of the RA case definition, and the denominator used, i.e. the exact amount of person years (PY) or census count data.Objectives:To investigate the incidence and prevalence of RA in the adult Danish population using four different case definitions and two different denominator strategies.Methods:Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…RA can occur in patients of any age, but the peak onset was between the ages of 70 and 74 in both sexes. 1 Sex was a known risk factor for RA, with an approximately twofold higher incidence in women compared with men. 1 23–25 Current and previous smoking were associated with a higher risk of RA in both sexes, with both duration and intensity of importance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…RA can occur in patients of any age, but the peak onset was between the ages of 70 and 74 in both sexes. 1 Sex was a known risk factor for RA, with an approximately twofold higher incidence in women compared with men. 1 23–25 Current and previous smoking were associated with a higher risk of RA in both sexes, with both duration and intensity of importance.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Sex was a known risk factor for RA, with an approximately twofold higher incidence in women compared with men. 1 23–25 Current and previous smoking were associated with a higher risk of RA in both sexes, with both duration and intensity of importance. 3 4 Thus, Liu et al conducted a cohort study among US women and showed that increased duration of smoking cessation was associated with a lower risk of overall RA in women, nevertheless, a higher risk of overall RA was still detectable after 30 years of smoking cessation compared with never smokers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations